The Position of Debt Collectors in the Implementation of Parate Execution of Fiduciary Guarantees Based on Law Number 42 of 1999 concerning Fiduciary Guarantees - Noor, Aslan; Chandra, Levina Abigail; Manurung, Norika; Sule, Aprilia Maharani (Dinasti Research, 2024)
Fiduciary guarantees in Indonesia are regulated in Law Number 42 of 1999. This guarantee provides security for creditors by binding movable property, both tangible and intangible, as well as immovable property, especially buildings that cannot be encumbered with mortgage rights. Debt collectors have an important role in the debt settlement process through parate execution, which is a direct execution of the fiduciary guarantee object without the need to go through court. The purpose of this research is to identify and analyze in depth the challenges faced in the implementation of existing laws, particularly in the context of parate execution by debt collectors. This research aims to document the weaknesses in the law that allow such violations to occur and explore more effective legal solutions. This research uses a legal research method that uses normative juridical research, which is research intended to conduct a study of the application of rules or norms in positive law. The result of this research is that the implementation of parate execution in fiduciary guarantees often involves debt collectors who have an important but controversial role, often causing abuse of authority and violations of human rights. Although regulations already exist, challenges still arise such as human rights violations, lack of legal understanding among debt collectors, and suboptimal supervision and law enforcement.